Bacteria transported by horseflies (Diptera: Tabanidae) in the northeast of Pará State, Brazil - Luz-Alves, Willy Cristiano; Gorayeb, Inocêncio de Sousa; Silva, José Caetano Lima; Loureiro, Edvaldo Carlos Brito (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
Insects of the family Tabanidae (Diptera), known as horseflies, are considered potential pests of man and domestic animals because of the hematophagic behavior of the females. They are capable of carrying virus, bacteria, and helminths, because these pathogens adhere to their piercing-sucking mouthparts. Horseflies were captured in peri-urban and forested areas, using Malaise traps and horses. After their identification, these horseflies were dissected and submitted to bacteriological study of the entire body, of the body surface, of mouth parts, and of the intestine. After isolation of bacterial colonies in cultures with blood agar, MacConkey, and Chapman, these were identified by biochemical tests. A total of 400 tabanid specimens of 18 species were collected, including: Dichelacera bifacies, Leucotabanus exaestuans, Tabanus antarcticus, T. occidentalis var. dorsovittatus. The 24 most frequently found bacterial species were: Staphylococcus spp., Streptococcus spp., Enterobacter cloacae, and Serratia marcescens. This study is the first on species of bacteria found in South American tabanids. The species S. marcescens, Staphylococcus aureus, and Escherichia coli are considered the most problematic in epidemiological terms, and these have been found in the following tabanid species: T. occidentalis var. dorsovittatus, T. olivaceiventris, T. indecisus, T. trivittatus, and T. sorbillans. The body surface of the tabanids was found to harbor more bacteria than other areas of the body.
Keywords: Insecta; Diptera; Tabanidae; Bacteria; Amazon Basin